Naphthalene ball poisoning: a rare cause of acquired methaemoglobinaemia. (25th May 2016) - Deo, Prateek; Sahu, Kamal Kant; Dhibar, Deba Prasad; Varma, Subhash Chander
Abstract : A 15-year-old boy presented to emergency services with accidental naphthalene ball ingestion. Following consumption he developed methaemoglobinaemia, massive intravascular haemolysis and acute kidney injury. He had no history suggestive of congenital haemoglobin M disease. Development of severe methaemoglobinaemia and intravascular haemolysis is quite unusual after consumption of a single ball of naphthalene. The patient was managed with ascorbic acid and intravenous N-acetyl cysteine. He also required haemodialysis for acute kidney injury that developed secondary to pigment nephropathy.